Educational (Mis)match and skill utilization in Germany: Assessing the role of worker and job characteristics - Daniela Rohrbach-Schmidt; Michael Tiemann (Journal for Labour Market Research, 2016)
This paper provides precise figures on the incidence and wage penalties of mismatching in Germany. We use the BIBB/BAuA Employment Survey 2006 to compute two different measures of person-to-job matching. A first measure indicates an educational (mis)match, i.e., whether a worker's attained level of education corresponds to the qualificational requirements of his or her job. Second, - and different from most other studies - we observe a skill (mis)match that reflects the correspondence between the skills of the job holder and the skill requirements of the job. We explore whether and the extent to which results on mismatch differ between these measures and explain the probability of being (mis)matched by different sets of worker and job characteristics. We also examine wage penalties for mismatching in Germany, considering a large number of controls for workers and, in addition to most earlier studies, job heterogeneity; we use random intercept models with workers nested in occupations. Our results indicate that large shares of over- or under-educated workers in Germany have skills that correspond to the skill requirements of their jobs. Furthermore, there are workers perfectly matched with respect to their education who, nevertheless, feel under- or over-challenged by their jobs' skill requirements. Random intercept models reveal that beyond worker characteristics, i.e., human capital compensation (heterogeneous ability) and career mobility rationalities, job characteristics play a role in the mismatching variance and its real or apparent wage penalties.
Keywords: I21; J23; J24; 330; mismatch; unterwertige Beschäftigung; adäquate Beschäftigung; BIBB/BAuA-Erhebung; Einkommenseffekte; Überqualifikation; Beschäftigungsentwicklung; matching; Unterqualifikation; Tätigkeitsmerkmale; Unterforderung